Hubungan Tingkat Pendidikan dan Penghasilan Pasien dengan Persepsi Pasien Tentang Mutu Pelayanan Kesehatan di Puskesmas Baki Kabupaten Sukoharjo - Listiani, Ida, Supratman, M.Kep, Ph.D (2017)
Perception has a very important role in evaluating the quality of health care, because it based on a good perception from the patient to the quality of service will affect the patient satisfaction and lead to a positive image to the health service. The purpose of this study was to determine the relation between education level and patient's income with the perception of the patient about the quality of health services in the Baki society health center Sukoharjo. This research is a correlational research with cross sectional approach. These samples included 100 respondents with an accidental sampling technique. Gauges in this study using questionnaires. The analyses of this research include univariat analysis and bivariate analysis using chi-square test. The results of the analysis through chi-square test between the patient's education to the patients' perceptions showed p = 0.008, and between patients' income to the patients' perceptions showed p = 0.000. So, we can conclude that there is significant correlation between patient's education and patients' income to the patients' perceptions about the quality of health services at the health center to health center Baki. The suggestion is they need to organize and improve the training of the officer suitable to their profession, in an order to improve the capabilities, skills and knowledge of the officers who will impact on improving the quality of health services.